POTENSI PEDAGOGIS METODE SARISWARA MELALUI PERMAINAN TIMBRE DALAM MENSTIMULUS KEMAMPUAN KERJA SAMA SISWA KELAS V SD - Adzani, Zahira Hasyidan; Resa Respati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Collaborative ability is an essential 21st-century skill that needs to be stimulated at the elementary school level through meaningful learning. This study aims to describe the collaborative ability of fifth-grade students at SDN 1 Kalangsari after implementing the Sariswara Method through timbre games. The study employed a descriptive quantitative approach with a One-Shot Case Study design. The research subjects were 58 fifth-grade students at SDN 1 Kalangsari, Tasikmalaya City. Data were collected through an observation sheet with 15 indicators covering five aspects of cooperation: positive interdependence, face-to-face promotive interaction, individual accountability, social skills, and group processing. Data analysis was conducted descriptively using ideal mean and ideal standard deviation categorization. The results showed that the average final score reached 85.00 with an achievement percentage of 85.00%. As many as 53 students (91.4%) were in the Very High category and 5 students (8.6%) in the High category. The aspect of positive interdependence obtained the highest mean score (94.2%), while face-to-face promotive interaction obtained the lowest (65.1%). These findings indicate that the Sariswara Method through timbre games is effective in stimulating collaborative ability among elementary school students.